Asian Flu or Wall Street Virus? : Price and Volatility Spillovers of the Tech and Non-Tech Sectors in the United States and Asia - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2002)
This paper, using T-GARCH models, finds that the United States has been the major source of price and volatility spillovers to stock markets in the Asian region during three different periods in the last decade: the pre-Long Term Capital Management crisis period, the "tech bubble" period, and the "stock market correction" period. Hong Kong SAR , Japan, and Singapore also were important spillover sources within the Asian region and affected United States to a lesser degree during the "stock market correction" period. There is also evidence of structural breaks in the stock price and volatility dynamics induced during the "tech bubble" period.